Hubungan status gizi dan pola makan dengan kejadian hipertensi pada penduduk dewasa - Mulyani Mulyani; Nur Husnul Khatimah; Hairunnisah Hairunnisah; Muammar Iksan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension is a non-communicable disease with increasing prevalence and is a major risk factor for cardiovascular disease. Excessive nutritional status and unhealthy diet are modifiable risk factors that need to be studied to support hypertension prevention efforts. Purpose: To analyze the relationship between nutritional status and dietary patterns and the incidence of hypertension in the adult population. Method: A quantitative analytical design with a cross-sectional approach was used, with a sample of 92 respondents selected using simple random sampling. The study was conducted in the working area of ​​the Belo Community Health Center, Bima Regency, during May and June 2026. Nutritional status data were obtained through body mass index (BMI), dietary patterns were measured using a semi-quantitative food frequency questionnaire (SQ-FFQ), and blood pressure was measured using a sphygmomanometer. Data analysis included univariate and bivariate analyses using the chi-square test with a 95% significance level (α=0.05). Results: The majority of respondents were overweight (37.0%), had poor diet (76.1%), and had hypertension (59.8%). The analysis showed a significant association between nutritional status and the incidence of hypertension (p<0.001). Respondents with overweight nutritional status had the highest proportion of hypertension (85.3%), followed by obesity (80.0%). Furthermore, there was a significant relationship between dietary habits and the incidence of hypertension (p=0.002), with respondents with poor dietary habits more likely to experience hypertension (68.6%) than respondents with good dietary habits (31.8%). Conclusion: There is a significant relationship between nutritional status and the incidence of hypertension, as well as a significant relationship between dietary habits and the incidence of hypertension, with p values ​​<0.001 and 0.002, respectively (α<0.05). Suggestion: It is recommended to use a larger sample size, a wider area, and the addition of other unexplored variables to obtain a more comprehensive picture of the factors associated with the incidence of hypertension. Keywords: Adults; Dietary Patterns; Hypertension; Nutritional Status.